High-temperature-resistant double-matrix solid electrolyte film and preparation method thereof
By preparing a high-temperature resistant dual-matrix solid electrolyte film, combining polymer matrix, inorganic ceramic particles and lithium source, the problem of degradation of traditional solid electrolyte performance at high temperatures is solved, and good ionic conductivity and electrochemistry at high temperatures are achieved Stability, suitable for wide temperature domain solid state batteries.
Patent Information
- Application Number
- CN202411436589.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional solid electrolyte materials show degradation in performance under high temperature conditions, especially the problems of reduced ionic conductivity, insufficient mechanical strength and poor interface compatibility, which makes it difficult for the performance of dual-matrix solid electrolytes to meet practical application needs at high temperatures.
A high-temperature resistant dual-matrix solid electrolyte film is adopted, including preparing a precursor solution, forming a film precursor and obtaining a high-temperature resistant dual-matrix solid electrolyte film through heat treatment, using polymer matrix, inorganic ceramic particles, lithium source and plasticization The agent is heat-cured in combination with a photoinitiator to form a thin film with good ionic conductivity and electrochemical stability.
It achieves good ionic conductivity and electrochemical performance at high temperatures, and is suitable for wide temperature domain solid-state batteries and electrochemical devices, extends service life and maintains good electrochemical performance.
Smart Images

Figure CN119253032A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a high-temperature resistant dual-matrix solid electrolyte film and a preparation method thereof. Background Art
[0002] With the continuous growth of global energy demand and the rapid development of renewable energy technology, efficient and stable energy storage systems have become the key. As the representative of the next generation of battery technology, solid-state batteries have attracted widespread attention due to their high energy density, long cycle life and safety. However, the development of solid-state batteries still faces many challenges, especially in terms of performance stability under high temperature environments.
[0003] Traditional solid electrolyte materials, such as pure polymer electrolytes or inorganic solid electrolytes, often show a trend of performance degradation under high temperature conditions. Although pure polymer electrolytes have good processability and flexibility, their ionic conductivity decreases significantly at high temperatures and their mechanical strength is insufficient. Although inorganic solid electrolytes have high ionic conductivity and mechanical strength, they are brittle, difficult to process, and have poor interface compatibility with electrode materials.
[0004] To overcome these shortcomings, researchers began to explore dual-matrix solid electrolyte materials. Dual-matrix solid electrolytes aim to achieve stable ion transport and mechanical properties at high temperatures by combining the advantages of different materials. However, the performance of most dual-matrix solid electrolytes at high temperatures is still difficult to meet the needs of practical applications, especially in terms of ionic conductivity, mechanical strength and interface stability. Summary of the invention
[0005] The purpose of the present invention is to provide a high temperature resistant dual matrix solid electrolyte film and a preparation method thereof, wherein the electrolyte film can have good ionic conductivity and electrochemical stability at high temperature.
[0006] To achieve the above object, the present invention provides a method for preparing a high temperature resistant dual matrix solid electrolyte film, comprising the following steps: S1. preparing a precursor solution; S2, forming the precursor solution into a film to form a thin film precursor; S3, curing the film precursor and then performing heat treatment to obtain a high temperature resistant dual matrix solid electrolyte film.
[0007] Preferably, the specific operation of preparing the precursor solution in S1 is: dissolving the polymer matrix in the solvent under the action of a magnetic stirrer and mixing evenly, then adding a lithium source to mix, and then adding inorganic ceramic particles, and after dissolution, adding a plasticizer and a photoinitiator to prepare a precursor solution.
[0008] Preferably, the specific operation of S2 is: the method of preparing the precursor solution into a membrane-like thin film precursor includes one of scraper, solution blending, melt blending or hot pressing molding.
[0009] Preferably, the curing method in S3 is one or two of heat curing, ultraviolet light curing, infrared light curing, and light curing + heat curing, and the heat treatment is drying in a vacuum drying oven at 50-70° C. for 1-3 hours.
[0010] Preferably, the polymer matrix in S1 is two of polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, polymethyl methacrylate, thermoplastic polyurethane elastomer and polyether sulfone, the inorganic ceramic particles are one or more of lithium aluminum titanium phosphate, LAGP, LLZO and LLZTO, and the lithium source is one of lithium perchlorate and lithium bis(trifluoromethanesulfonyl)imide.
[0011] Preferably, the mass ratio of the polymer matrix to the inorganic ceramic particles in S1 is (1-5):(0.1-1).
[0012] Preferably, the solvent in S1 is one or more of DMF, NMP and acetonitrile.
[0013] Preferably, the plasticizer in S1 is one or more of ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate, polyurethane acrylate, di(2-ethylhexyl) phthalate, dibasic fatty acid esters, and phthalates, and the photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone.
[0014] Preferably, the amount of the plasticizer in S1 is 50-70% of the total mass of the polymer matrix, and the amount of the photoinitiator is 1-10% of the total mass of the polymer matrix.
[0015] The present invention provides a high temperature resistant dual matrix solid electrolyte film, which is prepared by the above-mentioned method for preparing a high temperature resistant dual matrix solid electrolyte film.
[0016] Therefore, the present invention adopts the above-mentioned high-temperature resistant dual-matrix solid electrolyte film and its preparation method. The prepared solid electrolyte film can have good ionic conductivity and electrochemical properties at high temperatures, and is suitable for wide temperature range solid-state batteries and electrochemical devices.
[0017] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The surface and cross-sectional SEM morphology of a high temperature resistant dual matrix solid electrolyte film and a preparation method thereof according to an embodiment of the present invention; Figure 2 The Nyquist curve, DC polarization curve and electrochemical window curve of a solid electrolyte film of a high temperature resistant dual matrix solid electrolyte film and a preparation method thereof according to an embodiment of the present invention; Figure 3 is a thermogravimetric analysis curve of a solid electrolyte film of a high temperature resistant dual matrix solid electrolyte film and a preparation method thereof according to an embodiment of the present invention; Figure 4 The present invention discloses a high temperature resistant dual matrix solid electrolyte film and a method for preparing the same, and discloses a solid state battery having a discharge capacity at different current densities at 60°C and a discharge capacity after 100 cycles at a current density of 0.2C. DETAILED DESCRIPTION
[0019] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0020] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0021] Example The present invention provides a method for preparing a high temperature resistant dual matrix solid electrolyte film, comprising the following steps: S1. Prepare a precursor solution; dissolve the polymer matrix in a solvent under the action of a magnetic stirrer at 40-60°C and mix evenly, then add a lithium source and mix, then add inorganic ceramic particles, and after dissolution, add a plasticizer (50-70% of the total mass of the polymer matrix) and a photoinitiator (3-5% of the total mass of the polymer matrix) to prepare a precursor solution.
[0022] Plasticizers can improve flexibility, making the film softer and more bendable, and plasticizers help reduce the melt viscosity of the polymer and improve fluidity, making the processing easier and reducing defects such as cracks. The right amount of plasticizer can affect the arrangement of polymer chains, sometimes forming a microstructure that is more conducive to ion transport, which may improve the ionic conductivity of the electrolyte membrane.
[0023] Photoinitiators absorb light energy and convert into free radicals or acids, which in turn initiate polymerization reactions and quickly convert liquid precursors into solid films. This process is fast and environmentally friendly, and can effectively improve production efficiency. Through the photocuring process, the curing time and degree of the film can be precisely controlled, which helps to form a uniform and dense film structure. The cross-linked network structure formed by photocuring enhances the chemical and thermal stability of the electrolyte membrane, which is conducive to maintaining good performance and extending the service life during the battery charge and discharge cycle.
[0024] The polymer matrix is two of polyacrylonitrile (PAN), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), polymethyl methacrylate (PMMA), thermoplastic polyurethane elastomer (TPU), and polyether sulfone (PES); the inorganic ceramic particles are one or more of lithium aluminum titanium phosphate (LATP), LAGP, LLZO, and LLZTO; and the lithium source is one of lithium perchlorate and lithium bis(trifluoromethanesulfonyl)imide.
[0025] Polymers are easy to process and can be formed into uniform, continuous films by various methods such as solution casting, spraying, and spin coating, which is conducive to large-scale production and control of film thickness and morphology. By selecting different types of polymers and doping with appropriate lithium salts or other additives, the ionic conductivity of polymer electrolytes can be adjusted and the electrochemical performance of batteries can be optimized.
[0026] When the polymer matrix is PAN and PVDF-HFP, the mass ratio of the two is (1-5):(9-5), wherein the amount of lithium perchlorate used is 30-50% of the total mass of the two polymers, and the amount of inorganic ceramic particles added after dissolution is 5-20% of the total mass of the two polymer matrices, and stirring is carried out for 4-6 hours.
[0027] The mass ratio of the polymer matrix to the inorganic ceramic particles is (1-5):(0.1-1), and the solvent is one or more of DMF, NMP and acetonitrile.
[0028] S2. The precursor solution is made into a film by scraper, solution blending, melt blending or hot pressing to form a thin film precursor. The scraper is 100-200μm, and the plasticizer is ethoxylated trimethylolpropane triacrylate (ETPTA), 1,6-hexanediol diacrylate (HDDA), polyurethane acrylate (PUA), di(2-ethylhexyl) phthalate (DEHP), dibasic fatty acid esters (DOS / DOZ / DOA / DBS), phthalates ( The photoinitiator is one or more of DOP / DBP / DIBP / DCHP, and the photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone (1173), 1-hydroxycyclohexyl phenyl ketone (184), 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO), ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L), and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (659).
[0029] S3, after curing the film precursor, heat treatment is performed to obtain a high temperature resistant dual matrix solid electrolyte film, the curing method is one or two of heat curing, ultraviolet light curing, infrared light curing, light curing + heat curing, and the heat treatment is placed in a vacuum drying oven at 50-70°C for 1-3 hours. The curing operation can transform the liquid or semi-solid precursor into a solid form, giving it a certain shape and mechanical strength.
[0030] Embodiment 1 The present invention provides a method for preparing a high temperature resistant dual matrix solid electrolyte film, comprising the following steps: S1. Prepare the precursor solution: dissolve PAN and PVDF-HFP in DMF at a mass ratio of 3:7 on a magnetic stirrer at 45°C and mix well, then add lithium perchlorate (30% of the total mass of PAN and PVDF-HFP) and mix, then add LLZTO (10% of the total mass of PAN and PVDF-HFP), stir for 3 hours, add ETPTA and PUA (50% of the total mass of PAN and PVDF-HFP) after dissolution, stir for 5 minutes, then add 1173 (5% of the total mass of PAN and PVDF-HFP) to prepare the precursor solution.
[0031] S2. Use a 100 μm scraper to make the precursor solution into a thin film precursor.
[0032] S3. The film precursor is passed through a UV light curing machine and then heat-treated to obtain a high-temperature resistant dual-matrix solid electrolyte film. The heat treatment is to place it in a vacuum drying oven at 60° C. and dry it for 1 hour.
[0033] In order to verify the feasibility of the solid electrolyte film prepared by the method of the present invention, the morphology of the solid electrolyte film was observed by a scanning electron microscope (SEM); the ionic conductivity, lithium ion migration number and electrochemical window were tested using a DH-7000 electrochemical workstation; the high-temperature residual content of the solid electrolyte film was analyzed using a TGA system in the temperature range of 30-800°C; and the electrochemical performance was tested using a Xinwei battery testing system.
[0034] Figure 1 (a) shows the surface morphology of the prepared solid electrolyte film. Figure 1 (b) is the cross-sectional SEM morphology of the prepared solid electrolyte film. It can be seen from the figure that the pore structure is uniform and the thickness is about 35μm.
[0035] Figure 2 (a) is the Nyquist curve of the film. Figure 1 (b) and Figure 2 From (a) in the figure, it can be concluded that the ionic conductivity of the film is 1.58×10 -4 S / cm; Figure 2 (b) is the DC polarization curve and impedance spectrum of the solid electrolyte film, which shows that the film has a lithium ion migration number of 0.47. Figure 2 (c) in the figure is the electrochemical window of the solid electrolyte film, which has an electrochemical window of 4.2V.
[0036] Figure 3 The thermogravimetric analysis curve of the film shows that after 800°C, the solid electrolyte film still has a residual rate of 35.7%. Figure 4 The discharge specific capacity of the solid-state battery with solid electrolyte film at different current densities at 60°C and the discharge specific capacity after 100 cycles at a current density of 0.2C are shown. It can be concluded that the solid-state battery has a high discharge specific capacity (0.1C@169mAh / g and 1C@123mAh / g) and a good cycle life. Specifically, the capacity retention rate is 93.3% after 100 cycles at 0.2C.
[0037] Embodiment 2 S1. Prepare the precursor solution: dissolve PEO and PVDF-HFP in DMF at a mass ratio of 4:6 on a magnetic stirrer at 50°C and mix well, then add lithium perchlorate (40% of the total mass of PEO and PVDF-HFP) and mix, then add LLZTO (10% of the total mass of PEO and PVDF-HFP), stir for 5 hours, add ETPTA and PUA (60% of the total mass of PEO and PVDF-HFP) after dissolution, stir for 10 minutes, then add 184 (4% of the total mass of PEO and PVDF-HFP) to prepare the precursor solution.
[0038] S2. Use a 200 μm scraper to make the precursor solution into a thin film precursor.
[0039] S3. The film precursor is passed through a UV light curing machine and then heat-treated to obtain a high-temperature resistant dual-matrix solid electrolyte film. The heat treatment is to place it in a vacuum drying oven at 60° C. and dry it for 2 hours.
[0040] Embodiment 3 S1. Prepare the precursor solution: dissolve PMMA and PVDF-HFP in DMF at a mass ratio of 4:6 on a magnetic stirrer at 60°C and mix well, then add lithium perchlorate (30% of the total mass of PMMA and PVDF-HFP) and mix, then add LLZTO (10% of the total mass of PMMA and PVDF-HFP), stir for 6 hours, add ETPTA and PUA (50% of the total mass of PMMA and PVDF-HFP) after dissolution, stir for 15 minutes, then add TPO (3% of the total mass of PMMA and PVDF-HFP) to prepare the precursor solution.
[0041] S2. Use a 200 μm scraper to make the precursor solution into a thin film precursor.
[0042] S3. The film precursor is passed through a UV light curing machine and then heat-treated to obtain a high-temperature resistant dual-matrix solid electrolyte film. The heat treatment is to place it in a vacuum drying oven at 60° C. and dry it for 3 hours.
[0043] Therefore, the present invention adopts the above-mentioned high-temperature resistant dual-matrix solid electrolyte film and its preparation method. The prepared solid electrolyte film can have good ionic conductivity and electrochemical properties at high temperatures, and is suitable for wide temperature range solid-state batteries and electrochemical devices.
[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high temperature resistant dual matrix solid electrolyte film, characterized in that: The following steps are involved: S1. preparing a precursor solution; S2, forming the precursor solution into a film to form a thin film precursor; S3, curing the film precursor and then performing heat treatment to obtain a high temperature resistant dual matrix solid electrolyte film.
2. The method for preparing a high temperature resistant dual matrix solid electrolyte film according to claim 1, characterized in that: The specific operation of S1 preparing the precursor solution is: dissolving the polymer matrix in the solvent under the action of a magnetic stirrer and mixing evenly, then adding a lithium source to mix, and then adding inorganic ceramic particles, and after dissolution, adding a plasticizer and a photoinitiator to prepare a precursor solution.
3. The method for preparing a high temperature resistant dual matrix solid electrolyte film according to claim 2, characterized in that: The specific operation of S2 is: the method of preparing the precursor solution into a membrane-like thin film precursor includes one of scraper, solution blending, melt blending or hot pressing molding.
4. The method for preparing a high temperature resistant dual matrix solid electrolyte film according to claim 3, characterized in that: The curing method in S3 is one or two of heat curing, ultraviolet light curing, infrared light curing, and light curing + heat curing. The heat treatment is drying in a vacuum drying oven at 50-70°C for 1-3 hours.
5. The method for preparing a high temperature resistant dual matrix solid electrolyte film according to claim 4, characterized in that: The polymer matrix in S1 is two of polyacrylonitrile, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, polymethyl methacrylate, thermoplastic polyurethane elastomer and polyether sulfone, the inorganic ceramic particles are one or more of lithium aluminum titanium phosphate, LAGP, LLZO and LLZTO, and the lithium source is one of lithium perchlorate and lithium bis(trifluoromethanesulfonyl)imide.
6. The method for preparing a high temperature resistant dual matrix solid electrolyte film according to claim 5, characterized in that: The mass ratio of polymer matrix to inorganic ceramic particles in S1 is (1-5):(0.1-1).
7. The method for preparing a high temperature resistant dual matrix solid electrolyte film according to claim 6, characterized in that: The solvent in S1 is one or more of DMF, NMP and acetonitrile.
8. The method for preparing a high temperature resistant dual matrix solid electrolyte film according to claim 7, characterized in that: The plasticizer in S1 is one or more of ethoxylated trimethylolpropane triacrylate, 1,6-hexanediol diacrylate, polyurethane acrylate, di(2-ethylhexyl) phthalate, dibasic fatty acid esters, and phthalates, and the photoinitiator is one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, ethyl 2,4,6-trimethylbenzoylphenylphosphonate, and 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone.
9. The method for preparing a high temperature resistant dual matrix solid electrolyte film according to claim 8, characterized in that: The amount of plasticizer in S1 is 50-70% of the total mass of the polymer matrix, and the amount of photoinitiator is 1-10% of the total mass of the polymer matrix.
10. A high temperature resistant dual matrix solid electrolyte film, characterized in that: The film is prepared by the method for preparing a high temperature resistant dual matrix solid electrolyte film as described in claim 9.
Citation Information
Patent Citations
Micro-nano porous structure polymer electrolyte membrane used for lithium ion battery and method of producing the same
CN101552359A
Multi-component solid electrolyte and preparation method and application thereof
CN110994012A
Composite solid-state electrolyte membrane for solid-state battery and preparation method of composite solid-state electrolyte membrane
CN117219876A
Composite solid electrolyte film, preparation method thereof and solid-state battery
CN118136941A
Nanofiller-doped gel polymer electrolyte film, preparation method thereof and lithium metal battery
CN118380646A
